Academic freedom in the United States after Garcetti v. Ceballos - Lopez, Manuel Triano (Language and Law / Linguagem e Direito, 2017)
This paper focuses on the constitutional limits of instructor speech at public post-secondary institutions of learning in the United States. Specifically, the paper attempts to clarify these boundaries after the U.S. Supreme Court’s uncertain ruling in Garcetti v. Ceballos (2006). In that case, a narrow 5-4 majority held that the government – in its capacity as employer – may discipline an employee for communications made pursuant to his/her official duties when that speech undermines the government’s mission of delivering ecient services to the public. Garcetti would uphold the government’s adverse employment decision even if the employee’s controversial speech dealt with issues of relevance to the community. The Garcetti majority, however, declined to decide whether the ruling would also extend to “speech related to scholarship of teaching”, that is, whether Garcetti’s “official-duties” standard would apply to a particular group of public employees: teachers and professors. This uncertainty is compounded by the indecisive jurisprudence of the Court over the beneffciary of academic freedom. Whereas some decisions seem to uphold an individual academic freedom – i.e., the teacher’s liberty to seek and disseminate truth without fear of retaliation – other opinions have argued for an institutional type of academic freedom, whereby the public institution of learning – not the individual – decides what to teach and how to teach it. The analysis concludes with advice to faculty members of public post-secondary institutions so that they may protect themselves from the risk of adverse employment decisions justified by the Supreme Court.